Laparoscopic uterine artery occlusion for the treatment of symptomatic uterine fibroids - Weihong Yang, M.D; Ning Luo, M.D; Zhongping Cheng, M.D., PhD (Wolters Kluwer Medknow Publications, 2016)
With the development of gynecologic laparoscopy technology in recent years, uterine artery occlusion by laparoscopy (UAOL) has become a primary treatment for symptomatic uterine fibroids. Uterine artery occlusion by laparoscopy to treat uterine fibroids has favorable clinical outcomes such as relieving menometrorrhagia, decreasing uterine volume, and reducing the recurrence rate of fibroids. However, the therapeutic mechanism of UAOL remains unclear. It may be that the mechanism of UAOL is mostly associated with the uterine blood supply and uterine intramural arterial paths and with the difference between the uterine myometrium and fibroid tissues in the coagulation-fibrinolysis system. Therefore, this study reviewed and generalized many documents on the clinical effects and therapeutic mechanism of UAOL.